2000
DOI: 10.1105/tpc.12.12.2351
|View full text |Cite
|
Sign up to set email alerts
|

A Mutation in the Arabidopsis HYL1 Gene Encoding a dsRNA Binding Protein Affects Responses to Abscisic Acid, Auxin, and Cytokinin

Abstract: Both physiological and genetic evidence indicate interconnections among plant responses to different hormones. We describe a pleiotropic recessive Arabidopsis transposon insertion mutation, designated hyponastic leaves ( hyl1 ), that alters the plant's responses to several hormones. The mutant is characterized by shorter stature, delayed flowering, leaf hyponasty, reduced fertility, decreased rate of root growth, and an altered root gravitropic response. It also exhibits less sensitivity to auxin and cytokinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
266
3
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 450 publications
(280 citation statements)
references
References 82 publications
9
266
3
2
Order By: Relevance
“…It was demonstrated that SE also functions in miRNA processing through interacting with HYL1, which acts solely in miRNA biogenesis (Lu and Fedoroff 2000;Han et al 2004;Vazquez et al 2004;Grigg et al 2005;Lobbes et al 2006;Yang et al 2006;Fang and Spector 2007;Dong et al 2008;Laubinger et al 2008). Although there is no evidence that the THO complex plays a direct role in miRNA processing in metazoa, the observed genetic interaction between emu and se-1 prompted us to further examine a potential role for EMU in miRNA biogenesis.…”
Section: Genetic Interactions Between Emu and Mirna Mutantsmentioning
confidence: 99%
“…It was demonstrated that SE also functions in miRNA processing through interacting with HYL1, which acts solely in miRNA biogenesis (Lu and Fedoroff 2000;Han et al 2004;Vazquez et al 2004;Grigg et al 2005;Lobbes et al 2006;Yang et al 2006;Fang and Spector 2007;Dong et al 2008;Laubinger et al 2008). Although there is no evidence that the THO complex plays a direct role in miRNA processing in metazoa, the observed genetic interaction between emu and se-1 prompted us to further examine a potential role for EMU in miRNA biogenesis.…”
Section: Genetic Interactions Between Emu and Mirna Mutantsmentioning
confidence: 99%
“…As the first three proteins have been the subjects of a previous review [40], we describe them only briefly. abh1, sad1, and hyl1 mutants all show hypersensitivity to ABA during seed germination, but hyl1 and sad1 mutants appear to have more pleiotropic phenotypes [41][42][43]. The HYL1 protein contains two dsRBDs [41].…”
Section: Signalingmentioning
confidence: 99%
“…abh1, sad1, and hyl1 mutants all show hypersensitivity to ABA during seed germination, but hyl1 and sad1 mutants appear to have more pleiotropic phenotypes [41][42][43]. The HYL1 protein contains two dsRBDs [41]. Both ABH1 and SAD1 appear to be the only Arabidopsis orthologs of subunits of basic RNA-processing machineries in yeast and metazoans [42,43].…”
Section: Signalingmentioning
confidence: 99%
“…hyl1 affects leaf development, apical dominance and hor-mone sensitivity. It exhibits hyper-sensitivity to abscisic acid and hypo-sensitivity to cytokinin and auxin (Lu Plant Cell 2000) [57], (Vazquez Mol Cell 2004) [58]. Complete loss of HEN1 and HYL1 function causes phenotypes that are much less severe than those of ago1 or dcl1 mutants, indicating that HEN1 and HYL1 are redundant with other genes for miRNA biogenesis and function.…”
Section: Hyponastic Leaves1 (Hyl1)mentioning
confidence: 99%